Predictive and sensitive biomarkers for thyroid dysfunctions during treatment with immune‐checkpoint inhibitors. Issue 5 (17th March 2020) - Kurimoto, Chiaki; Inaba, Hidefumi; Ariyasu, Hiroyuki; Iwakura, Hiroshi; Ueda, Yoko; Uraki, Shinsuke; Takeshima, Ken; Furukawa, Yasushi; Morita, Shuhei; Yamamoto, Yuki; Yamashita, Shimpei; Katsuda, Masahiro; et al.
Abstract: Immune‐related adverse events (irAEs) are often seen during immune‐checkpoint inhibitor (ICI) treatment of various malignancies. Endocrine irAEs including thyroid dysfunctions are the most common irAEs, but their biomarkers remain unclear. In order to identify individuals who are susceptible to thyroid irAE for earlier diagnosis and appropriate follow‐up, the current study is aimed to investigate biomarkers of thyroid irAE. Herein, patients with advanced malignant diseases who received ICIs treatment were prospectively studied. Clinical and laboratory examination, thyroid function, and autoantibodies were evaluated at baseline, and every 4 wk after first treatment with ICIs. Cytokines/chemokines were measured at baseline and at 4 wk. In vivo effects of ICIs on experimental autoimmune thyroiditis were evaluated. Twenty‐six patients with malignant diseases who received ICIs treatment were enrolled in the study. Patients were divided into two groups: those who developed thyroid irAE, and those without irAEs. Comparing the two groups, early increase (≤4 wk) in serum thyroglobulin (Tg) levels and thyroid autoantibodies was seen in thyroid irAE ( P  < .05). Notably, higher levels of serum IL‐1β, IL‐2, and GM‐CSF at baseline, and early decrease of IL‐8, G‐CSF, and MCP‐1 were significantly associated in the development of thyroid irAE ( P  < .05). In vivo effects of anti‐PD‐1 antibody on deterioration of mice experimental thyroiditis were seen. In conclusion, early change in Tg, thyroid autoimmunity, and cytokine levels might indicate development of thyroid irAE. Pre‐existing thyroid autoimmunity might be involved with the development of thyroid irAE. Potential application of these factors as surrogate biomarkers for tumor therapy was indicated.